Vernacular architecture in Chazhashi Settlement, Upper Svaneti, Georgia - Carlos, Gilberto Duarte (2022)
Since 2006, Escola Superior Gallaecia (Portugal), University of Florence (Italy), and Universitat Politècnica de València (Spain), with partners as CRAterre-ENSAG (France), the University of Cagliari (Italy), and Ecole d’Avignon (France), have been working together, for the enhancement and protection of vernacular heritage and earthen architecture. As key-institutions in the area, they share high standards and common values, in order to address and achieve fundamental research, capacity building, learning experiences, relevant outcomes, contributing for a broader and deeper knowledge on vernacular heritage and earthen architecture. Several projects were developed among the partners, throughout the years. This was just possible by running together for European Union funded research, and successfully achieving it, by undertaking relevant contribution to knowledge, as well as comprehensive scientific dissemination. This was the case of the following projects: Terra Incognita (2006-2008); Earthen Domes & Habitat – A building tradition between East and West (2008-2010); Terra (in)cognita/Terra Europae (2009-2011: culture-terra-incognita.org); VerSus – From Vernacular Heritage to Sustainable Architecture (2012- 2014: esg.pt/versus); 3DPAST – Living and virtual visiting European World Heritage (2016-2020: esg.pt/3dpast); and VERSUS+ | Heritage for People (2019-2023: esg.pt/versus-plus). Other key-projects have been also developed through National Funding Agencies for Science, Research and Technology as it was the case of: Seismic-V – Local Seismic Culture in Portugal (esg.pt/seismic-v); PRIN – Scientific, experimental and tacit knowledge and conservation actions of Earthen Architectural Heritage in Southern Italy; ResTAPIA – Restoration of rammed earth in Iberia Peninsula (www.restapia. es); SOStierra – Restoration and Rehabilitation of traditional earthen architecture in Iberia Peninsula (sostierra.blogs.upv.es) and RISK-Terra (https://riskterra.blogs.upv.es); among others. The focus of the distinct researches was to address: a state of the art of earthen architecture in Europe (both Terra Incognita projects); to define principles from vernacular heritage that contribute to sustainable architecture (VerSus project & VERSUS+ project); to enhance the quality of vernacular architecture and its World Heritage character (3DPAST); to distinguish seismic retrofitting in vernacular architecture, in order to pro-actively strength dwellings facing earthquakes (Seismic-V).